Application of the C45 Algorithm to Predict Student Academic Scores - Andi Ernawati; Zulham Sitorus; Ananda Aulia; Ayu Ofta (Bulletin of Information Technology (BIT), 2024)
Student grades are the results of teaching and learning activities on a campus. So you can know your target for completing your studies. This research uses the C4.5 Algorithm which can help predict the results of student assessments. The dataset consists of student achievement index, place of residence, discipline, lecturer's role in lectures. From 40 datasets we have obtained a decision on student academic achievement and obtained performance results from accuracy results of 86.36% with class precision predicate Yes=84.62%, No=88.89% and class recall Yes=91.67%, No=80.00%.